The Influence of Electronic Word of Mouth (E-Wom) 0n Reuse Intentions with User Trust as a Mediation Variable on OVO Application Users in Semarang City - Azizah, Ofinatul; Firdaus , Firdaus (Economics and Business International Conference Proceeding, 2024)
This research aims to determine the effect of electronic word of mouth (E-WOM) on reuse intentions with user trust as a mediating variable in OVO application users. For the research population carried out in the city of Semarang, sampling was taken using a purposive sampling technique, namely using criteria such as how long the application has been used and whether or not one has used the application. The data used is primary data in the form of the results of distributing questionnaires to respondents via Google Form on a scale likert of 1-5. The data analysis method in this research uses SmartPLS-SEM (Partial Least Square - Structural Equation Modeling). Testing of this research model was carried out on two measurement models, namely the outer model and the inner model. The results of this research show that Electronic Word of Mouth (E-WOM) has a positive and significant effect on Intention to Reuse which is mediated by user trust, either directly or indirectly. This shows that by increasing positive E-WOM on OVO, this can make consumers use OVO products again.